Acetabular complications are the most common cause for revision surgery following proximal femoral endoprosthetic replacement: what is the best bearing option in the primary and revision setting?. (1st October 2021) - Lex, Johnathan Robert; Evans, Scott; Parry, Michael C.; Jeys, Lee; Stevenson, Jonathan D.
Abstract : Aims: Proximal femoral endoprosthetic replacements (PFEPRs) are the most common reconstruction option for osseous defects following primary and metastatic tumour resection. This study aimed to compare the rate of implant failure between PFEPRs with monopolar and bipolar hemiarthroplasties and acetabular arthroplasties, and determine the optimum articulation for revision PFEPRs. Methods: This is a retrospective review of 233 patients who underwent PFEPR. The mean age was 54.7 years (SD 18.2), and 99 (42.5%) were male. There were 90 patients with primary bone tumours (38.6%), 122 with metastatic bone disease (52.4%), and 21 with haematological malignancy (9.0%). A total of 128 patients had monopolar (54.9%), 74 had bipolar hemiarthroplasty heads (31.8%), and 31 underwent acetabular arthroplasty (13.3%). Results: At a mean 74.4 months follow-up, the overall revision rate was 15.0%. Primary malignancy (p < 0.001) and age < 50 years (p < 0.001) were risk factors for revision. The risks of death and implant failure were similar in patients with primary disease (p = 0.872), but the risk of death was significantly greater for patients who had metastatic bone disease (p < 0.001). Acetabular-related implant failures comprised 74.3% of revisions; however, no difference between hemiarthroplasty or arthroplasty groups (p = 0.209), or between monopolar or bipolar hemiarthroplasties (p = 0.307), was observed. There was greater radiological wear in patients with longer follow-up and primary bone malignancy. Re-revision rates following a revision PFEPR was 34.3%, with dual-mobility bearings having the lowest rate of instability and re-revision (15.4%). Conclusion: Hemiarthroplasty and arthroplasty PFEPRs carry the same risk of revision in the medium term, and is primarily due to acetabular complications. There is no difference in revision rates or erosion between monopolar and bipolar hemiarthroplasties. The main causes of failure were acetabular wear in the hemiarthroplasty group and instability in the arthroplasty group. These risks should be balanced and patient prognosis considered when contemplating the bearing choice. Dual-mobility, constrained bearings, or large diameter heads (> 32 mm) are recommended in all revision PFEPRs. Cite this article: Bone Joint J  2021;103-B(10):1633–1640.